An Acetamide Derivative as a Camptothecin Sensitizer for Human Non-Small-Cell Lung Cancer Cells through Increased Oxidative Stress and JNK Activation. (24th October 2016) - Chou, Han-Lin; Fong, Yao; Lin, Hsin-Hsien; Tsai, Eing Mei; Chen, Jeff Yi-Fu; Chang, Wen-Tsan; Wu, Chang-Yi; David Wang, Hui-Min; Huang, Hurng-Wern; Chiu, Chien-Chih
Abstract : In recent years, combination chemotherapy is a primary strategy for treating lung cancer; however, the issues of antagonism and side effects still limit its applications. The development of chemosensitizer aims to sensitize chemoresistant cancer cells to anticancer drugs and therefore improve the efficacy of chemotherapy. In this study, we examined whether N-[2-(morpholin-4-yl)phenyl]-2-{ 8-oxatricyclo[7.4.0.0, 2, 7]trideca-1(9), 2(7), 3, 5, 10, 12-hexaen-4-yloxy} acetamide (NPOA), an acetamide derivative, sensitizes human non-small-cell lung cancer (NSCLC) H1299 cells towards camptothecin- (CPT-) induced apoptosis effects. Our results demonstrate that the combination of CPT and NPOA enhances anti-lung-cancer effect. The cytometer-based Annexin V/propidium iodide (PI) staining showed that CPT and NPOA cotreatment causes an increased population of apoptotic cells compared to CPT treatment alone. Moreover, Western blotting assay showed an enhancement of Bax expression and caspase cascade leading to cell death of H1299 cells. Besides, CPT and NPOA cotreatment-mediated disruption of mitochondrial membrane potential (MMP) in H1299 cells may function through increasing the activation of the stressed-associated c-Jun N-terminal kinase (JNK). These results showed that NPOA treatment sensitizes H1299 cells towards CPT-induced accumulation of cell cycle S phase and mitochondrial-mediated apoptosis through regulating endogenous ROS and JNK activation. Accordingly, NPOA could be a candidate chemosensitizer of CPT derivative agents such as irinotecan or topotecan in the future.